2015
DOI: 10.1088/0957-4484/26/11/115203
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale conductive pattern of the homoepitaxial AlGaN/GaN transistor

Abstract: The gallium nitride (GaN)-based buffer/barrier mode of growth and morphology, the transistor electrical response (25-310°C) and the nanoscale pattern of a homoepitaxial AlGaN/GaN high electron mobility transistor (HEMT) have been investigated at the micro and nanoscale. The low channel sheet resistance and the enhanced heat dissipation allow a highly conductive HEMT transistor (I ds > 1 A mm −1 ) to be defined (0.5 A mm −1 at 300°C). The vertical breakdown voltage has been determined to be ∼850 V with the vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Despite much researches on inorganic nanotubes, very few experiments have been performed on GaN nanotubes (GaNNT) as sensors. In group III-nitrides, GaN has been extensively studied experimentally and theoretically due to their diverse application in electronic devices, such as quantum-point lasers, LEDs, optoelectronics, transistors, and others [44][45][46][47][48]. Liu et al have reported that GaN catalyzes the direct hydrogenation of CO 2 to dimethyl ether with a CO-free selectivity of about 80% [49].…”
Section: Introductionmentioning
confidence: 99%
“…Despite much researches on inorganic nanotubes, very few experiments have been performed on GaN nanotubes (GaNNT) as sensors. In group III-nitrides, GaN has been extensively studied experimentally and theoretically due to their diverse application in electronic devices, such as quantum-point lasers, LEDs, optoelectronics, transistors, and others [44][45][46][47][48]. Liu et al have reported that GaN catalyzes the direct hydrogenation of CO 2 to dimethyl ether with a CO-free selectivity of about 80% [49].…”
Section: Introductionmentioning
confidence: 99%